let i, j, k be Nat; :: thesis: for G being Go-board st 1 <= j & j <= width G & 1 <= i & i <= k & k <= len G holds

(G * (i,j)) `1 <= (G * (k,j)) `1

let G be Go-board; :: thesis: ( 1 <= j & j <= width G & 1 <= i & i <= k & k <= len G implies (G * (i,j)) `1 <= (G * (k,j)) `1 )

assume that

A1: 1 <= j and

A2: j <= width G and

A3: 1 <= i and

A4: i <= k and

A5: k <= len G ; :: thesis: (G * (i,j)) `1 <= (G * (k,j)) `1

(G * (i,j)) `1 <= (G * (k,j)) `1

let G be Go-board; :: thesis: ( 1 <= j & j <= width G & 1 <= i & i <= k & k <= len G implies (G * (i,j)) `1 <= (G * (k,j)) `1 )

assume that

A1: 1 <= j and

A2: j <= width G and

A3: 1 <= i and

A4: i <= k and

A5: k <= len G ; :: thesis: (G * (i,j)) `1 <= (G * (k,j)) `1